(untitled) (Journal of the College of Basic Education, 2024)
valley Basin Fouad is one of the basins located east of the Western Desert, which is located within Karbala Governorate and slopes northeast of the Razaza Depression. The basin occupies an area of ​​(259.22 km2). The aim of this study is the possibility of investing in the natural resources of limestone, sand, clay, and gypsum, as they are of economic value for the study area to benefit from. Including in the construction industries, especially the possibilities of investing in surface and groundwater resources. Groundwater is one of the important sources in the basin and knowing the physical and chemical characteristics of the wells, which number (18), in order to determine the suitability of water for drinking for humans and evaluate irrigation water for agricultural purposes. The study concluded a number of Among the recommendations that we can invest naturally and humanly.